2021
DOI: 10.3390/molecules26030531
|View full text |Cite
|
Sign up to set email alerts
|

Spin Exchanges between Transition Metal Ions Governed by the Ligand p-Orbitals in Their Magnetic Orbitals

Abstract: In this review on spin exchanges, written to provide guidelines useful for finding the spin lattice relevant for any given magnetic solid, we discuss how the values of spin exchanges in transition metal magnetic compounds are quantitatively determined from electronic structure calculations, which electronic factors control whether a spin exchange is antiferromagnetic or ferromagnetic, and how these factors are related to the geometrical parameters of the spin exchange path. In an extended solid containing tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Consequently, the overlap density between the magnetic orbitals of Cu1 and Cu2 becomes nonzero due to a nonzero overlap density between the x 2 − y 2 and 3 z 2 − r 2 orbitals of the Cu2 site. 33–35 As a consequence, the spin exchange between the adjacent Cu 2+ sites becomes ferromagnetic in AMP[CuCl 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the overlap density between the magnetic orbitals of Cu1 and Cu2 becomes nonzero due to a nonzero overlap density between the x 2 − y 2 and 3 z 2 − r 2 orbitals of the Cu2 site. 33–35 As a consequence, the spin exchange between the adjacent Cu 2+ sites becomes ferromagnetic in AMP[CuCl 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present work makes it clear that the use of a correct spin lattice is critical in describing the properties of a magnetic material. As a criterion for finding a proper spin lattice, the geometrical pattern of magnetic ion arrangement can be grossly misleading because a spin lattice is decided by the geometrical pattern of the strong spin exchange paths [3,4,19]. If volborthite were to be treated as a spin-frustrated kagomé lattice model, the S = 1/2 antiferromagnetic uniform Heisenberg chain behaviors of its magnetic susceptibility and magnetization are exotic and novel, as are its specific heat anomalies below 1.5 K. By the same token, all other magnetic properties of volborthite not explained by a spin-frustrated kagomé lattice model would be novel and surprising.…”
Section: Discussionmentioning
confidence: 99%
“…However, our work showed that each kagomé layer of Cu 2+ ions consists of very-weakly interacting two-leg spin ladders, so the seemingly exotic magnetic properties previously attributed to magnetic frustration are simply explained by a well-studied S = 1/2 antiferromagnetic uniform Heisenberg chain model. To find a correct spin lattice for any given magnetic material, it is necessary to evaluate the relative strengths of various possible spin exchanges of a given magnetic system by using an unbiased and straightforward method such as the energy-mapping analysis, based on first principles DFT calculations [3,4,19,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reflect that the magnetic orbitals of a cation M forming an ML n polyhedron with surrounding ligands are given by d-states of ML n , in which the p-orbitals of L are combined out-of-phase with the d-orbitals of M, and that all types of spin exchanges are governed largely by the ligand p-orbitals of the magnetic orbitals. The qualitative aspects of spin exchanges were reviewed by Myung-Hwan Whangbo, Hyun-Joo Koo and Reinhard K. Kremer [2], in which they discuss how the qualitative trends in spin exchanges are related to the arrangements of the magnetic orbitals, providing the structure-property relations with which to understand the magnetic properties of complex magnetic solids.…”
Section: Contributions In the Area Of Spin Exchanges And Magnetismmentioning
confidence: 99%